1998
DOI: 10.1007/s00585-998-1283-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects in the ionosphere-thermosphere response to the precipitation and field-aligned current variations in the cusp region

Abstract: Abstract. The seasonal e ects in the thermosphere and ionosphere responses to the precipitating electron¯ux and ®eld-aligned current variations, of the order of an hour in duration, in the summer and winter cusp regions have been investigated using the global numerical model of the Earth's upper atmosphere. Two variants of the calculations have been performed both for the IMF B y < 0. In the ®rst variant, the model input data for the summer and winter precipitating¯uxes and ®eld-aligned currents have been take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The thermospheric (O)/(N 2 ) ratio depletion, especially in the Asian sector, is apparent from Figure 8. Joule heating of the upper polar neutral atmosphere from enhanced storm time FACs and increased particle precipitation, cause storm time neutral winds which could transport N 2 molecules from the lower atmosphere to higher altitudes, consequently magnification of recombination rate in the F region and thus the (O)/(N 2 ) ratio decreased, leading to negative ionospheric storm (Anderson et al., 1998; Namgaladze et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The thermospheric (O)/(N 2 ) ratio depletion, especially in the Asian sector, is apparent from Figure 8. Joule heating of the upper polar neutral atmosphere from enhanced storm time FACs and increased particle precipitation, cause storm time neutral winds which could transport N 2 molecules from the lower atmosphere to higher altitudes, consequently magnification of recombination rate in the F region and thus the (O)/(N 2 ) ratio decreased, leading to negative ionospheric storm (Anderson et al., 1998; Namgaladze et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This allows the modeling of the upper atmospheric behavior during substorms via the UAM simulations. The results were presented in [4,[48][49][50][51][52][53] including the cusp and auroral oval behavior, energetic magnetospheric electron precipitations, electric fields, current wedge and internal atmospheric gravity waves generation. The main role of the thermospheric heating due to the soft electron precipitation was shown for the thermosphere substorm effects.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this field is influenced by various factors such as solar wind, Earth's magnetic field, and atmospheric winds. In the summer and winter cusp regions, it is found that ionospheric disturbances are more intensive in the winter cusp region, associated to higher electric field variations and electron flux precipitation [13]. During quiet periods, changes in the Sun's direction incorporated in the conductivity model indicates that the peak of the electric field at sunset is highest during the equinox and significant during the solstices.…”
Section: Introductionmentioning
confidence: 99%